Pengaruh Sistem Patroli Jalan Tol Terhadap Kepuasan Pelanggan Yang Mengalami Gangguan Perjalanan Di Jalan Tol Surabaya Gempol (studi kasus pada ruas jalan tol surabaya gempol) - Daengs, Achmad (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2013)
The great existing of human resources should be changed to become useful assets for development. For a variety of expertise, skills and opportunities should be focused on human resources, according to their biological and spiritual abilities. The careful and prudent action must be taken in human resources to become productive and beneficial assets in development. Thus the choices of the companyâ€™s development strategy are directed to the achievement of problem coping in specific areas. Therefore, PT. Jasa Marga (Persero) Branch of Surabaya-Gempol has a special department in charge to develop, train, manage and optimize Human Resources of their employees. Based on description above, then the formulation of the problem is â€œHow far the effect of competency-based training that consists of knowledge, skills, ability to employeesâ€™ work quality of PT. Jasa Marga (Persero) Branch of Surabaya-Gempolâ€. Based on formulation of the problem and the hypothesis which stated, then after conducting the analysis and hypothesis testing, the results are obtained: The value of Adjusted R Square is 0.891 which showed that 89.10% of the change in Y value is affected by the three independent variables, while the remaining of 10.90% are affected by other things outside of the three independent variables under this study. Key words: Speed, Friendliness, Accuracy, Convenience, and Completeness.